Perlindungan Hukum atas Inkonsistensi Penerapan Unsur “Persamaan pada Pokoknya” dalam Penegakan Hukum Sengketa Merek - Arnanto, Kevin Rayindra; Hervina Puspitosari (UNES Law Review, 2024)
The aim of this research is to analyze the realization of legal certainty in the inconsistent application of the "equality in essence" element in trademark disputes and repressive legal protection for inconsistencies in trademark disputes by fulfilling the element of "equality in essence". The research method used is normative juridical, with a statutory, legal conceptual and case approach. Data comes from secondary data, including primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is descriptive analytical. The results of the research found that the description of the element of "substantial similarity" in brands is where there are similarities caused by the presence of dominant elements between one brand and another, giving the impression of similarities, whether in terms of shape, way of placement, way of writing or a combination of elements, or similarities in speech sounds. The existence of inconsistencies shows that legal certainty has not been realized. Repressive legal protection for inconsistencies in trademark disputes by fulfilling the element of "equality in essence" can be realized by providing preventive protection so that the problem does not occur again, which is realized by standardizing law enforcement procedures, strengthening legislation, supervision and outreach. Apart from these preventive measures, repressive protection against the occurrence of these inconsistency problems can be carried out by filing ordinary legal remedies in the form of appeals and cassation, as well as extraordinary legal remedies in the form of judicial review.